Hypocalcemic tetany associated with simultaneous administration of cimetidine and nifedipine: a case report - Yihienew M. Bezabih; Mekides A. Bimrew; Woldesellassie M. Bezabhe (Journal of Medical Case Reports, 2023)
Abstract Background Acute hypocalcemia is generally caused by a sudden drop in serum calcium ion and presents with a mild or severe form of tetany. Even though the occurrence of hypocalcemia is well documented with certain drugs such as calcium chelators, bisphosphonates, and cisplatin, it is a very unusual and poorly documented adverse event with cimetidine and nifedipine. Here, we present a case of severe hypocalcemic tetany during simultaneous administration of cimetidine and nifedipine in a hypertensive patient with dyspepsia. Case presentation A 46-year-old known human immunodeficiency virus patient from Ethiopia on antiretroviral therapy over the past 14 years presented to the emergency department with acute exacerbation of dyspepsia and hypertensive urgency. She was given intravenous cimetidine (400 mg) and oral nifedipine (30 mg) simultaneously. One hour after the administration of these two drugs, she developed severe hypocalcemic tetany with carpopedal spasm, involuntary plantar flexion, and muscle spasms. She also had severe retrosternal chest pain and shortness of breath. Her blood pressure was 160/110 mmHg during the attack and she had no skin changes, such as urticaria. She was immediately given 1 g of calcium gluconate intravenously over 30 minutes. The carpopedal spasm progressively decreased during calcium gluconate administration. An hour later, she completely regained voluntary movement of her fingers and feet. The chest pain persisted, but resolved over the next 12 hours. The patient was discharged home after 2 days of observation. This is an unusual adverse effect that needs caution during concomitant administration of these drugs. Conclusions Severe hypocalcemic tetany can occur with concomitant administration of cimetidine and nifedipine. Immediate treatment with calcium gluconate quickly reverses this adverse event. Concomitant administration of these drugs should be done with caution or be avoided if possible.